ANALISIS TUJUAN PENGELOLAAN DAN KEBUTUHAN DALAM PENGEMBANGAN DANAU SENTANI JAYAPURA - Walukow, Auldry F. (Bumi Lestari; Vol 11 No 1 (2011), 2011)
The destruction of nature is caused by the wrong human’s point of view towards neighbourhoods. Ecofeminism assumes the caused factor of nature destruction comes from patriarchy culture which more on dualistic logic, hierarchy and the fight for domination. The thought of patriarchy causes destruction of nature and oppression of woman. Ecofeminism thought is interesting to be researched because it offers alternative vision which more sociable and gender balanced. The aim of this research is to explicit, critically evaluate, formulate concept of ecofemisthics ethics thought comprehensively and to reveal new vision relating to keep forest preservation. The chosen literature is analyzed using philosophy method: description, interpretation, and holistic. The result of this research shows that nature preservation is lasting and oppression towards woman is stopped if society abandoned patriarchy thought. Ecofeminism develops the concept of care ethics holistically, interactively, non-reduction, and participatively. Principe of ethics which need to be concerned are responsibility towards the whole biosphere, cosmic solidarity, keeping balance with nature, equal relation, careens and simplicity. The excess of ecofeminism succed in realizing the danger of patriarchy thought towards woman and nature. The weakness of it is that it generalizes and universalizes feministhics values uniformity towards all women instead of a priory negative towards the quality of masculinity values. Ecofeminism develops human moral responsibility based on women special experiences.
Keywords: institution; responsibility; co-management; Sentani Lake